Where you live matters: Challenges and opportunities to address the urban–rural divide through innovative secondary cardiac rehabilitation programs. (19th June 2013) - Sangster, Janice; Furber, Susan; Phongsavan, Philayrath; Allman‐Farinelli, Margaret; Redfern, Julie; Bauman, Adrian
Abstract: Objective: Only one third of clinically eligible patients attend a cardiac rehabilitation (CR) program. Few studies have looked at participation in rural cardiac patients. This paper examines the risk profile and participation in CR of rural and urban residents with cardiac disease who enrolled in a telephone coaching program. Design, setting and participants: Comparison of baseline characteristics of 173 urban and 140 rural Australians referred to CR, and who enrolled in a telephone‐based coaching program. Main outcome measures: Sociodemographic characteristics, health behaviours and participation in CR programs. Results: Rural residents were more likely to enrol in a telephone coaching secondary prevention program (44.7% versus 25.5%, P < 0.001) than urban residents. For those enrolling in the telephone‐based program, rural participants were more likely to be obese (42.0% rural versus 28.8% urban, P = 0.02), to rate their health as fair or poor (45% versus 24.3%, P < 0.001) and less likely to be sufficiently physically active (35.3% versus 53.2%, P = 0.002), or follow a special diet for their heart (40.0% versus 56.6%, P = 0.003) compared with urban participants. Those who attended a CR program were more likely to be from an urban location and live closer to a CR program. Conclusions: Rural participants in this study had poorer health profiles and attendance at outpatient CR compared with urban participants. This poses challenges for the provision of secondary prevention programs for rural cardiac patients and highlights opportunities to trial innovative delivery models, such as telephone‐based programs, to reach people that would otherwise not have access.